Enhanced lipid production by Yarrowia lipolytica cultured with synthetic and waste-derived high-content volatile fatty acids under alkaline conditions - Ruiling Gao; Zifu Li; Xiaoqin Zhou; Wenjun Bao; Shikun Cheng; Lei Zheng (Biotechnology for Biofuels, 2020)
Abstract Background Volatile fatty acids (VFAs) can be effective and promising alternate carbon sources for microbial lipid production by a few oleaginous yeasts. However, the severe inhibitory effect of high-content (> 10 g/L) VFAs on these yeasts has impeded the production of high lipid yields and their large-scale application. Slightly acidic conditions have been commonly adopted because they have been considered favorable to oleaginous yeast cultivation. However, the acidic pH environment further aggravates this inhibition because VFAs appear largely in an undissociated form under this condition. Alkaline conditions likely alleviate the severe inhibition of high-content VFAs by significantly increasing the dissociation degree of VFAs. This hypothesis should be verified through a systematic research. Results The combined effects of high acetic acid concentrations and alkaline conditions on VFA utilization, cell growth, and lipid accumulation of Yarrowia lipolytica were systematically investigated through batch cultures of Y. lipolytica by using high concentrations (30–110 g/L) of acetic acid as a carbon source at an initial pH ranging from 6 to 10. An initial pH of 8 was determined as optimal. The highest biomass and lipid production (37.14 and 10.11 g/L) were obtained with 70 g/L acetic acid, whereas cultures with > 70 g/L acetic acid had decreased biomass and lipid yield due to excessive anion accumulation. Feasibilities on high-content propionic acid, butyric acid, and mixed VFAs were compared and evaluated. Results indicated that Y X/S and Y L/S of cultures on butyric acid (0.570, 0.144) were comparable with those on acetic acid (0.578, 0.160) under alkaline conditions. The performance on propionic acid was much inferior to that on other acids. Mixed VFAs were more beneficial to fast adaptation and lipid production than single types of VFA. Furthermore, cultures on food waste (FW) and fruit and vegetable waste (FVW) fermentate were carried out and lipid production was effectively improved under this alkaline condition. The highest biomass and lipid production on FW fermentate reached 14.65 g/L (Y X/S: 0.414) and 3.20 g/L (Y L/S: 0.091) with a lipid content of 21.86%, respectively. By comparison, the highest biomass and lipid production on FVW fermentate were 11.84 g/L (Y X/S: 0.534) and 3.08 g/L (Y L/S: 0.139), respectively, with a lipid content of 26.02%. Conclusions This study assumed and verified that alkaline conditions (optimal pH 8) could effectively alleviate the lethal effect of high-content VFA on Y. lipolytica and significantly improve biomass and lipid production. These results could provide a new cultivation strategy to achieve simple utilizations of high-content VFAs and increase lipid production. Feasibilities on FW and FVW-derived VFAs were evaluated, and meaningful information was provided for practical applications.